Al-Qur'an illiteracy eradication with animated video in Sukarami, Bengkulu City - Lety Febriana; Desi Firmasari; Amnah Qurniati (Community Empowerment, 2022)
The development of various methods for learning the Qur'an illustrates the importance of Qur'anic education and the public's awareness of the need for it. In reality, however, many people are still unable to read the Qur'an properly. One option is to use engaging learning media such as Macromedia Flash Player animated videos. The PKM-S program's goal is to eliminate illiteracy in the Qur'an while also increasing insight, knowledge, and understanding of the significance of reading it. Training and mentoring are used to carry out service activities. This training activity is expected to increase partners' empowerment by raising morale about God's love and truth, as well as increasing knowledge of how to read the Qur'an in a way that is good and correct according to the rules.